2018
DOI: 10.1097/md.0000000000009491
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diagnostic and therapeutic vitrectomy for vitreous opacity associated with uveitis with various etiologies

Abstract: Vitreous opacity (VO) is a common feature of intermediate uveitis, posterior uveitis, and panuveitis. Fundus observation is critical for determining the etiology of uveitis, however, is often interfered with VO. In these clinical settings, vitrectomy contributes to a correct diagnosis and guides alternative management strategies. The purpose of this study was to evaluate the diagnostic yield and surgical outcome of vitrectomy in uveitic patients with VO and compare the visual outcome between infectious and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…8,[18][19][20] For vitrectomy, about 50% of patients had vitreous opacity, and malignant lymphoma and sarcoidosis seemed to be the underlying diseases, although vitrectomy for inflammatory eyes with vitreous opacity of unknown etiology has been reported. 21 In the present study, the mean VA was significantly improved after vitrectomy, but 14.2% of patients required the reoperation, which seems a high incidence. In our study, fungal endophthalmitis was observed in 25 patients, which seemed higher.…”
Section: Discussioncontrasting
confidence: 44%
“…8,[18][19][20] For vitrectomy, about 50% of patients had vitreous opacity, and malignant lymphoma and sarcoidosis seemed to be the underlying diseases, although vitrectomy for inflammatory eyes with vitreous opacity of unknown etiology has been reported. 21 In the present study, the mean VA was significantly improved after vitrectomy, but 14.2% of patients required the reoperation, which seems a high incidence. In our study, fungal endophthalmitis was observed in 25 patients, which seemed higher.…”
Section: Discussioncontrasting
confidence: 44%
“…The role of PPV in the management of IU has been reported by many authors before whether as a diagnostic or a therapeutic procedure and was associated with a decrease in the severity of inflammation, recurrence rate and the need for immunosuppressives postoperatively [22][23][24]. The surgery is commonly performed as a therapeutic approach in uveitic cases complicated by epimacular membrane, TRD, rhegmatogenous retinal detachment and vitreous hemorrhage [21].…”
Section: Discussionmentioning
confidence: 97%
“…The surgery is commonly performed as a therapeutic approach in uveitic cases complicated by epimacular membrane, TRD, rhegmatogenous retinal detachment and vitreous hemorrhage [21]. Yet, even in the absence of these complications, PPV was also found to be beneficial in improving visual activity and decreasing inflammation in cases of persistent vitreous opacities despite full systemic medical therapy [22,23]. In cases of noninfectious IU, it has been suggested that vitrectomy may be effective in improving vitreous inflammation by removing the antigenic load and reducing the levels of cytokines and interleukins that activate the inflammatory cascade [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It gives the additional advantage of potentially confirming a diagnosis. In a mixed series of infectious and noninfectious uveitis, a diagnosis was reached following vitreous analysis with culture, PCR, and cytokine analysis in 34 of 45 eyes (75%) [221]. Vision improved following vitrectomy in most eyes.…”
Section: Vitrectomymentioning
confidence: 99%